Debt Covenant Violations, Firm Financial Distress, and Auditor Actions - Bhaskar, Lori Shefchik; Krishnan, Gopal V.; Yu, Wei (Contemporary Accounting Research, 2017)
We conduct a comprehensive study on the associations between debt covenant violations (“violations”) and auditor actions for financially distressed and nondistressed firms. Our study is motivated by a lack of research on the consequences of violations resulting from auditors' actions. We find that firms with violations have significantly higher audit fees, a greater likelihood of receiving a going‐concern opinion, and a greater likelihood of experiencing an auditor resignation. Importantly, the positive associations hold for all types of firms, including financially nondistressed firms. In fact, we find that, after controlling for other financial information, the relation between violations and an increased likelihood of a going‐concern opinion is stronger for nondistressed versus distressed firms. Our evidence is consistent with belief‐revision research in auditing that finds auditors react more strongly to information that is inconsistent with their prior beliefs. This study provides further evidence on the indirect yet significant consequences of covenant violations on firms resulting from auditor actions.